Pineapple development and fruit quality under different weed control methods (Research, Society and Development, 2021)
Agricultural management strategies can improve production, especially in regions with critical environmental conditions for the development of agricultural crops, however, in plants such as pineapple, applied research to optimize production and fruit quality is still lacking. This work aimed to evaluate plant development and fruit quality of pineapple from Pérola and Vitória cultivars, submitted to two cultivation methods (with and without mulching) and two types of weeding (chemical and manual). The experiment was carried out in the North Region of Espírito Santo, in a randomized block design, in a 2x2x2 triple factorial scheme, where the cultivars Pérola and Vitória were evaluated, including or not mulching and chemical or manual weeding. Plants were evaluated for vegetative development, macro and micronutrient contents and SPAD index in leaf D. Firmness, mass, length, central diameter and physicochemical characteristics were evaluated. Under the edaphoclimatic conditions of the experiment, the cultivar Pérola had faster growth, but low soluble solids content (12º Brix) compared to ‘Vitória’, being indifferent to the type of weeding and mulching. The cv. Vitória produced fruits with greater firmness and soluble solids content of 16ºBrix, with important increments with the use of mulching and manual weeding, standing out in the physicochemical characteristics related to the quality of the fruits, which leads to the recommendation for its use of these techniques for its cultivation in the North Coast region of Espírito Santo.